Development of OrSAEv Model Learning: Preliminary Study of Students’ Prepareness Facing Volcanic Eruption Disaster - Madlazim; Wasis; Siti Nurvitasari (Studies in Learning and Teaching, 2021)
Geologically, Indonesia is a country prone to disasters, particularly volcanic eruptions. One of the steps that can be taken to minimize the impact of volcanic eruptions is through the education sector as foundation the knowledge, attitudes, and skills of students. Therefore, this study aims to determine the preparedness of students in dealing with volcanic eruptions based on aspects of knowledge about volcanic eruptions, responsiveness in dealing with volcanic eruptions, and evacuation skills in dealing with volcanic eruptions. The subjects of the study were 26 students from 8th grade at Junior High School of 1 Ngancar. Research method in this study is by interviews and tests. Samples of respondents were taken randomly based on suggestions from science teachers at Junior High School of 1 Ngancar. The results of the research that have been carried out are as follows: Student preparedness is still in the poor category, seen from the aspect of knowledge and skills in evacuation, while the aspect of disaster response attitudes shows conflicting results, where based on the test of disaster response attitudes, 83.3% is in the good category. However, based on interviews with science teachers, it shows that the facilities, and there has never been any socialization related to disaster mitigation in the school environment. Therefore, it is necessary to do an application test to find out whether disaster response attitudes are truly embedded in students.